A STUDY ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMAN 7 SIAK IN COMBINING SENTENCES USING RELATIVE PRONOUNS - Al Faruk, Salman; Prawati, Atni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research is a descriptive research that was conducted based on the problem occurred at the first years students of SMA 7 Siak; namely the students were lack in making sentences using relative pronouns that influence them got poor sore in test. Therefore, this research was aimed to find out on the ability of the first years students of SMA 7 Siak in combining sentences using relative pronouns. The participants were 35 students from first years of SMA 7 Siak. This research was conducted for about four months(February – May, 2015) and wad taken on April 6th and April 8th , 2015 at SMAN 7 Siak, Tut WuriHandayani street No.1, Kandis. The data collection technique was obtained through (1) try out which was applied to know the quality of the test items, particularly to determine the item difficulty and item discrimination and (2) test was done to measure students’ achievement. The research finding can briefly explain as follow: First the result of the test shows that the easiest relative pronouns is ‘where’ (average to good level), while the most difficult relative pronouns is ‘whom’ (poor level). It can be seen in the mean score for relative pronoun ‘where’ is 66,25 (average to good level) and the mean score for relative pronoun ‘whom’ is 34,38 (poor level).Keyword: relative pronouns, combining sentences.